Ocular Acanthamoebiasis in Iraq - Guirges, Sami Y.; Mousa, Ali A.A.; Al-Hadithi, Fakhri (Journal of the Faculty of Medicine Baghdad, 2008)
Free – living or limax amoebae are small free-living protozoans which exist in fresh water and soil environment. These amoebae were found infective to man causing a fatal disease affecting the central nervous system. Fowler and Carter were the first to report four fatal human cases of acute pyogenic meningitis caused by free-living amoebae1. The genera Naegleria and Acanthamoeba are incriminated in such infections2. Swimming in contaminated water has been frequently postulated as the way of infection through the intranasal mucosa. Sincethat time more than one hundred cases of primary amoebic meningoencephalitis were reported from different parts of the world. On the other hand, the free-living amoebae of thegenus Acanthamoeba are known to cause eye infection and keratitis3,4,5. The discovery of progressive corneal ulceration due to several species of Acanthamoeba were reported inmany parts of the world6,7. We describe here the first reported case of ocular acanthamoebiasis in Iraq due to the infection with Acanthamoeba sp.